Different Patterns of Mental Health Problems in Unaccompanied Refugee Minors (URM): A Sequential Mixed Method Study - Hanewald, Bernd; Knipper, Michael; Fleck, Werner; Pons-Kühnemann, Jörn; Hahn, Eric; Ta, Thi Minh Tam; Brosig, Burkhard; Gallhofer, Bernd; Mulert, Christoph; Stingl, Markus (Frontiers in Psychiatry, 2020)
Unaccompanied refugee minors (URM) represent one of the most vulnerable refugee groups due to their young age, developmental status and insufficient coping strategies. Clinical observations indicate that the frequency of mental health problems varies between different URM subgroups. In the present research project, clinical interviews as a source of qualitative data were combined with quantitative psychometric information in a mixed-method approach in order to study the patterns of mental health problems in 561 URM from four different language groups (Arabic, Farsi, Somali and Tigrinya) immediately after arrival in the host country (Germany). Qualitative analysis obtained as differentiating categories “language, countries of origin, age and gender”; quantitatively, the Refugee Health Screener (RHS-15) was applied. According to the positive screening results, the highest number of mental complaints was returned by children and adolescents speaking Farsi (65.9%) and Somali (65.8%). They were followed by URM speaking Arabic (49.4%) and Tigrinya (43.3%). The results were influenced not only by origin, but also by age (with higher burden among older Farsi-speaking URM) and gender (with higher burden among male URM). Although the prevalences in URM subgroups differ, the observed high rates of positive screening results in our sample of URM from Germany substantiate the need for early detection of mental complaints and appropriate mental health care for at least every second URM. Although the prevalences in URM subgroups differ, the observed high rates of positive screening results in our sample of URM from Germany substantiate the need for early detection of mental complaints and appropriate mental health care for at least every second URM.